2013
DOI: 10.7554/elife.00947
|View full text |Cite
|
Sign up to set email alerts
|

The ER–Golgi intermediate compartment is a key membrane source for the LC3 lipidation step of autophagosome biogenesis

Abstract: Autophagy is a catabolic process for bulk degradation of cytosolic materials mediated by double-membraned autophagosomes. The membrane determinant to initiate the formation of autophagosomes remains elusive. Here, we establish a cell-free assay based on LC3 lipidation to define the organelle membrane supporting early autophagosome formation. In vitro LC3 lipidation requires energy and is subject to regulation by the pathways modulating autophagy in vivo. We developed a systematic membrane isolation scheme to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
358
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(387 citation statements)
references
References 83 publications
20
358
1
3
Order By: Relevance
“…Ge et al [82] found that the membrane fraction from Atg5-knockout MEF cells, in which no LC3 conjugation occurs, can be conjugated with LC3 when incubated with the cytosol from wild type cells. Using this cell-free assay system, they further performed membrane fractionation and found that LC3 was preferentially conjugated with the membrane subfraction containing ERGIC marker proteins.…”
Section: The Er-golgi Intermediate Compartment (Ergic)mentioning
confidence: 99%
“…Ge et al [82] found that the membrane fraction from Atg5-knockout MEF cells, in which no LC3 conjugation occurs, can be conjugated with LC3 when incubated with the cytosol from wild type cells. Using this cell-free assay system, they further performed membrane fractionation and found that LC3 was preferentially conjugated with the membrane subfraction containing ERGIC marker proteins.…”
Section: The Er-golgi Intermediate Compartment (Ergic)mentioning
confidence: 99%
“…ATG14 and ATG5 puncta formation is associated with autophagy initiation (21,23). ATG5 puncta, which is usually used as a phagophore marker, also localized to LAPTM4B positive endosomes ( Fig.…”
Section: Significancementioning
confidence: 99%
“…However, the identity of nascent autophagosome structures such as PAS is pivotal to several crucial questions regarding autophagosome biogenesis, including the membrane deformation mechanism and the origin of the autophagosome membrane. Membrane sources, including the endoplasmic reticulum (ER), mitochondria, ER-mitochondria contact sites, ER-Golgi intermediate compartment, Golgi apparatus, and plasma membrane have been postulated to contribute to autophagosome formation in yeast and/or mammalian cells (Axe et al, 2008;Hayashi-Nishino et al, 2010a, 2010bHailey et al, 2010;Noda et al, 2011;Ohashi and Munro, 2010;Ravikumar et al, 2010;Ge et al, 2013;Hamasaki et al, 2013). In plants, however, most observations of autophagosome-related structures have been based on the classical features of autophagosomes: their isolated double-membrane appearance, enclosed autophagic cargos, and labeling with an autophagosome marker (Rose et al, 2006;Toyooka et al, 2006;Katsiarimpa et al, 2011;Takatsuka et al, 2011;Hanamata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%